Complications of radical and partial nephrectomy for renal cell carcinoma up to 7 cm - Marić Predrag; Jovanović Mirko; Milović Novak; Stamenković Dušica; Košević Branko; Aleksić Predrag; Cerović Snežana; Spasić Aleksandar; Simić Dejan; Rašković Jelena (Vojnosanitetski Pregled)
Background/Aim. Renal cell carcinoma (RCC) is the third most frequent urological carcinoma. Radical nephrectomy (RN) is considered as the gold standard in the treatment of localized RCC, but recently the use of minimally invasive techniques are more frequently used. The aim of this study is to determine is there a difference in the incidence of complications in the group of patients treated by RN and partial nephrectomy (PN) for renal cell carcinoma up to 7 cm. Methods. The retrospective study included the analysis of the medical history of patients surgically treated in the six years period. The inclusion criteria were RCC size up to 7 cm and no detectable metastasis. The exclusion criterion was the presence of a bilateral tumor. Intraoperative and early postoperative complications were followed-up. The Clavien- Dindo grade system was used for classification of surgical complications. Results. In six years period 481 (76.35%) radical transperitoneal nephrectomies and 149 (23.65%) partial nephrectomies were performed. Bilateral RCCs were verified in 2.06% (13/630), an initial metastatic disease in 15.8% (100/630) and lymph node involvement in 7.14% (45/630) of the patients and their data were not included in analysis. Therefore, data from 120 patients with RN and 97 patients with PN who fulfill inclusion criteria were analyzed. Complications were recorded in 29.5% (64/217) of patients. Significantly less patients had complications in the RN group [22.5 % (27/120)] compared to the PN group [38.1% (37/97)] (p = 0.006). These complications were mostly grade I and II. Complications grade III and IV were only present in the group of patients treated by PN. Conclusion. Based on our data in selected patients with renal cell carcinoma in stage T1, PN is a proper and safe choice. The patient must be involved in making the definitive decision of modalities of surgical treatment.